Management of Separated Endodontic Instrument and a Blocked Canal - A Case Report - Rai, Arbind; Ayer, Ashok; Vikram, Mannu (Journal of Nepalese Association of Pediatric Dentistry, 2022)
The fracture of endodontic instruments and canal blockage is a procedural problem creating a major obstacle to normal routine endodontic therapy. The separated instrument, particularly a broken file, leads to metallic obstruction in the root canal while canal blockage,caused by packing dentin chips and/or tissue debris, impedes efficient cleaning and shaping. Negotiating the canal and achieving patency is a must but when attempts fail to bypass such a fragment or gaining patency becomes difficult, it should be achieved by newer techniques and equipments. Dental operating microscope and ultrasonics have found indispensable applications in a number of dental procedures. This clinical casedemonstrates the usage of anultrasonic device under operative microscope in the removal of separated NiTi instrument and achieving patency in symptomatic premolars.